PENERAPAN SISTEM TERDISTRIBUSI BERBASIS ANDROID PADA APLIKASI PENJURIAN PERTANDINGAN TAEKWONDO - RIYAN; HERO; HARLIYUS (Jurnal PROCESSOR, 2019)
The taekwondo match is led by a referee and three judges in charge of giving scores to athletes who get points. The position of these judges is at the edge of the determined arena. The judging system requires many devices such as joy-stick, in-focus and a computer that each device must be connected to each other by using a wire, this method is felt to be less effective where the position of the cable should not be touched or trampled by the player or referee in the match area. To overcome this, it is necessary to design a judging system that utilizes Android with wireless networks to make it easier to give points. The judging process as described can be improved by utilizing information technology in the form of an Android smart phone for judging by using an input device in the form of an Android phone that serves to enter points that will later be displayed. The test results show that the application are more compatible with the World Taekwondo Competition Rules & Interpretation 2018 compared to the previous tools that have not been used in the latest regulations